1995
DOI: 10.1097/00000542-199505000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Linearly Reduces the Vasoconstriction and Shivering Thresholds 

Abstract: Advantages of this new model include its being nearly noninvasive and requiring relatively little core-temperature manipulation. Propofol only slightly alters the sweating threshold, but markedly reduces the vasoconstriction and shivering thresholds. Reductions in the shivering and vasoconstriction thresholds are similar; that is, the vasoconstriction-to-shivering range increases only slightly during anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(99 citation statements)
references
References 50 publications
3
92
0
4
Order By: Relevance
“…None of the patients from either group shivered in the PACU; this may be because of propofol [26], fentanyl [27] and tramadol [28] that have residual effects on the thermoregulatory control centre, including reduced shivering. Besides, the postoperative forced-air warming over the skin could also have prevented shivering.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients from either group shivered in the PACU; this may be because of propofol [26], fentanyl [27] and tramadol [28] that have residual effects on the thermoregulatory control centre, including reduced shivering. Besides, the postoperative forced-air warming over the skin could also have prevented shivering.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pharmacological agents 7,10,[16][17][18][19][20][21][22][23][24][25] (Table 2) that reduce the vasoconstriction and shivering thresholds have been used to manage shivering during therapeutic hypothermia. According to the ILCOR, 3 sedative and hypnotic agents are often used to decrease metabolic demand and facilitate mechanical ventilation in comatose patients who lack signs of awakening within the first 5 to 10 minutes after return of spontaneous circulation.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
“…Doses of 2.5 to 10 mg of midazolam are moderately effective in reducing shivering, although the drug also has a high sedative effect and a low risk of hypotension. 27 Matsukawa et al 25 reported that propofol linearly reduced the shivering threshold by 0.7ºC (SD, 0.1ºC) per microgram per milliliter, to a shivering threshold of 34.4ºC to 31.5ºC with doses of 2 to 8 µg/mL, respectively. However, a limitation in the use of propofol is the risk of hypotension.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
“…Isso não foi surpresa porque a resposta de regulação térmica é diminuída em idosos 15 . É difícil determinar fatores de risco independentes para tremores antes da intervenção cirúrgica, já que numerosas variáveis influenciam a regulação térmica no pós-operatório resultante dos anestésicos voláteis 32 ou venosos e dos sedativos 33 . Além disso, quase todos os fármacos usados regularmente pelos pacientes (anti-hipertensivos e antidiabéticos, derivados cumarínicos) parecem oferecer proteção significativa para tremores.…”
Section: Fisiopatologiaunclassified
“…This was not surprising, because thermal regulation response is decreased in the elderly 15 . It is difficult to determine independent risk factors for tremors before surgery, since several variables influence postoperative thermal regulation in the case of volatile 32 or intravenous anesthetics, and sedatives 33 . Besides, almost every drug used regularly by patients (antihypertensives, those used in the treatment of diabetes, and coumarin derivatives) seems to offer significant protection against tremors.…”
Section: Physiopathologymentioning
confidence: 99%